The practice of executive coaching to improve leadership capacity in academic deans at American higher education institutions. Issue 2 (3rd July 2019) - Bertrand, David W.
ABSTRACT: The history and sociology of faculty career transitions to academic deanships is an intriguing phenomenon, given that the skill sets of accomplished scholars vary immensely from the duties and responsibilities of academic deans. On top of that, today's academic deans continue to face particularly challenging leadership dilemmas. This exploratory, qualitative study sought to learn if executive coaching is an effective strategy to swiftly and ably prepare deans for the unique requirements of the position, as well as to equip them with and/or improve transformational leadership skills. Results were favourable towards coaching and showed associations in transformational leadership to be strongest in the component of intellectual stimulation. Deans also described improvements in empathetic behaviour, self-awareness and self-care – outcomes that suggest deans received value on a personal level and not just professionally. As perceived by the deans, coaches achieved these outcomes by the superior quality of their listening skills, their ability to offer useful perspectives, and by building trust. The information provided in this study might challenge institutions of higher education to consider executive coaching as a way to eliminate blind spots and address personal and organisational challenges that academic deans and other senior-level administrators encounter.